A user-centred personalised e-learning system - Nguyen, Thao; Chang, Vanessa (Victoria University of Technology, 2006)
The paper proposes a framework for understanding the factors that affect usability of e-learning. The framework can be applied to the development of (1) a formative usability evaluation method for e-learning systems and (2) personalisation rules for e-learning systems interface. The formative usability evaluation method is intended for the evaluation of e-learning systems during its development stages, from screen-based prototypes to near completion. The evaluation criteria will be customisable depending on contingent criteria such as user characteristics and e-learning system characteristics. A web-based prototype will be developed to allow the convenient implementation of the methodology. The personalisation rules for e-learning system is intended for the automatic adaptation of e-learning systems' interface to different users' preferences in order to maximise its usability and learnability for individual users.